Challenges in the implementation of urban redevelopment in Batu Gajah, District of Kinta, Perak / Suzıanawatı Hassan and Mohd Hasrol Haffiz Aliasak - Hassan, Suzıanawatı; Aliasak, Mohd Hasrol Haffiz (2018)
Redevelopment is an approach used by the government in developing existing urban areas. Redevelopment means an activity to change the physical structure of the urban area to overcome social, physical, economic and environmental problems in order to achieve the concept of highest and best use of land efficiencies and effectiveness. Urban redevelopment involves complicated issues for implementation in urban areas such as the process of land acquisition, residential resettlement, negotiations on investment, modifications of existing town plans, and financial aids. The challenges are being identified by conducting a semi-structured interview to the specified respondents. All the respondents from Majlis Daerah Batu Gajah, Pejabat Daerah dan Tanah Kinta and Penghulu Kanan Daerah Kinta agreed that scarcity of land is the main challenge for the implementation of urban redevelopment.. The process of redevelopment will require a long time to be executed; however is depends on the people's perceptions. People's perception are something that cannot be easily managed by the respondent. Thus, there must be cooperation between the Local Authority, owners of the land and properties; and the government to improve the identity of the urban area. Usually redevelopment will not take a long time to implement as compared with a new town. Redevelopment is intended to improve people's lives and improve the image of the urban areas of Batu Gajah Town.